Exploring the Mediating Role of Good Looking Appearance: How Do Brand and Customer Emotions Affect Impulse Buying? - Desak Made Febri Purnama Sari; Assyifa Nur Annisa Permana; ⁠I Gst Ayu Wirati Adriati; Ida Nyoman Basmantra (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Digitalization has given birth to new marketing strategies that are more interactive, one of which is through live streaming. The high consumer interaction in live streaming shows the significant attractiveness of the batik market. In addition, audience comments also show an emotional attachment to the product and the seller. This condition is related to the concept of emotional brand attachment, which is the emotional attachment of consumers to the brand. This study uses a quantitative approach with a survey method, which aims to test the relationship between variables through numerical data processing and statistical analysis. The results show that promotional strategies that combine emotional elements and visual aesthetics can effectively increase consumer interaction, engagement, and impulsive purchase impulses on social commerce platforms such as TikTok. Emotional and visual factors are important elements in shaping the impulse buying behavior of batik consumers on TikTok. Emotional brand attachment emerged as the most dominant variable that affects visual perception (good-looking appearance) and impulsive purchase decisions.